Adverse Pregnancy Outcomes Attributable to Socioeconomic and Ethnic Inequalities in England: A National Cohort Study. Issue 3 (24th September 2022) - Jardine, J.; Walker, K.; Gurol-Urganci, I.; Webster, K.; Muller, P.; Hawdon, J.; Khalil, A.; Harris, T.; van der Meulen, J.; ,
Abstract : ( Lancet . 2021;398:1905–1912) Pregnancy outcomes (eg, stillbirth, preterm birth, and neonatal and infant mortality) in high-income countries tend to be worse among patients from ethnic minority groups and lower socioeconomic status (SES) compared with White patients or patients of higher SES. While there are efforts to reduce these inequalities, more information is needed to understand which groups are most affected and how severe these gaps are. This national cohort study examined the socioeconomic and ethnic inequalities in the rates of fetal growth restriction (FGR), preterm birth, and stillbirth, accounting for health conditions at the beginning of pregnancy and complications that affect pregnancy.